2022
DOI: 10.1002/jhm.13030
|View full text |Cite
|
Sign up to set email alerts
|

Tell‐a provider about tele: Reducing overuse of telemetry across 10 hospitals in a safety net system

Abstract: Background: Telemetry is often a scarce resource at hospitals and is important for arrhythmia and myocardial ischemia detection. Overuse of telemetry monitoring leads to alarm fatigue resulting in failure to respond to arrhythmias, patient harm, and possible unnecessary testing.Methods: This quality improvement initiative was implemented across NYC Health and Hospitals, an 11-hospital urban safety net system. The electronic health record intervention involved the addition of a mandatory indication in the telem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 25 Similarly, a study that also implemented a ordering CDS and monitoring duration alert demonstrated a roughly 20% decrease in telemetry monitoring hours per patient encounter. 27 This study adds to the literature because it describes physician behavior, as well as highlights and describes some of the contextual factors for why some implementation strategies may be more effective than others. For example, the qualitative portion of this study demonstrated that when a physician is required to provide an indication for telemetry monitoring, this causes them to reflect and consider if telemetry monitoring is really warranted, thereby decreasing potentially unnecessary telemetry monitoring use.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Similarly, a study that also implemented a ordering CDS and monitoring duration alert demonstrated a roughly 20% decrease in telemetry monitoring hours per patient encounter. 27 This study adds to the literature because it describes physician behavior, as well as highlights and describes some of the contextual factors for why some implementation strategies may be more effective than others. For example, the qualitative portion of this study demonstrated that when a physician is required to provide an indication for telemetry monitoring, this causes them to reflect and consider if telemetry monitoring is really warranted, thereby decreasing potentially unnecessary telemetry monitoring use.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, our recent published successes in reducing overuse in our system shed some insights into implementation. 18,[22][23][24][25] In particular, EHR-based interventions, if developed well and tailored through expert stakeholder input, can bring forth a low-effort, highimpact change suited for large, resource-limited settings. An important concept is that order sets are effective only so much as clinicians use them.…”
Section: Discussionmentioning
confidence: 99%